Sustainability by Design: Embedding Green Principles into Digital Product Development (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study explores the integration of sustainability principles into digital product development. It aims to create a framework for embedding environmental, social, and economic sustainability within digital design practices. Using a descriptive qualitative method based on literature analysis and thematic review, this study identifies core challenges and strategies in applying sustainable design. Findings highlight that sustainability integration enhances product value, reduces carbon footprint, and supports the Sustainable Development Goals (SDGs). The study contributes to a better understanding of how organizations can balance innovation with sustainability in digital transformation.